Perencanaan Gambar Rainwater Harvesting Metode Roof Cacthment Dengan Desain Tropical Green Roof: (Studi Kasus: Gedung Penunjang Terpadu RSUD Waluyo Jati Kraksaan Kabupaten Probolinggo) - Bintang Mutiara Suli (Jurnal Vokasi Teknik Sipil, 2024)
Waluyo Jati Regional Hospital carries out continuous development to improve services to the community. This development has increased the volume of clean water needed to meet the water needs of Waluyo Jati Regional Hospital. This research aims to determine the planning drawings of a rainwater harvesting system that uses the roof method of the integrated supporting building at Waluyo Jati Regional Hospital with a tropical green roof design and to find out how much savings occur after implementing this system. This research uses a descriptive analysis method with a quantitative approach. Based on the results of research that has been carried out, it was found that the total area of the integrated support building at Waluyo Jati Regional Hospital was 656.21 m2 with a rainwater runoff discharge of 19.260 liters/hour and a rain intensity of 30,87 mm/hour. The size of the ground water tank used is 2,31 m long, 1,73 m wide and 2,89 m high. The savings after implementing the rainwater harvesting system using the roof catchment method with a tropical green roof design is that it can save PDAM water costs of IDR. 156,230/day.